2007
DOI: 10.1097/scs.0b013e31802d6e76
|View full text |Cite
|
Sign up to set email alerts
|

Somatic FGFR and TWIST Mutations are not a Common Cause of Isolated Nonsyndromic Single Suture Craniosynostosis

Abstract: Pathogenic mutations in FGFR2 and TWIST genes are detected in the majority of individuals with Crouzon, Pfeiffer, Apert, and Saethre-Chotzen syndromes. In contrast, mutations have been identified rarely in cases of nonsyndromic, single suture craniosynostosis. Recently, two studies confirming somatic mosaicism with local expression of an FGFR mutation have been reported. This study investigates whether somatic mosaicism could account for nonsyndromic, single suture craniosynostosis. Eight individuals with sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…In the vast majority of cases a genetic cause has not yet been identified. Seto et al [21] found a TWIST1 mutation in one of 83 scaphocephalic individuals, though other cohorts have not replicated this observation [22,23]. While Seto et al suggested a causative relationship, Kress et al in a similar case believed this to be a non-disease-causing polymorphism [24].…”
Section: Scaphocephalymentioning
confidence: 82%
See 1 more Smart Citation
“…In the vast majority of cases a genetic cause has not yet been identified. Seto et al [21] found a TWIST1 mutation in one of 83 scaphocephalic individuals, though other cohorts have not replicated this observation [22,23]. While Seto et al suggested a causative relationship, Kress et al in a similar case believed this to be a non-disease-causing polymorphism [24].…”
Section: Scaphocephalymentioning
confidence: 82%
“…McGillivray et al [25] suspect a major role of the FGFR2 gene in sagittal suture closure. Anderson et al [23] tested for somatic mutations of the FGFR and TWIST genes in the sutural tissue of 8 individuals with single suture craniosynostosis. None of the tissue samples exhibited any mutations of the genes in question.…”
Section: Scaphocephalymentioning
confidence: 99%
“…Consent was obtained following the guidelines of the Research Ethics Committee of the Children, Youth and Women’s Health Service, SA. Patients were genotyped for mutations in FGFR1-3 and TWIST [20]. Primary suture cells were obtained by collagenase digestion and explant culture [21].…”
Section: Methodsmentioning
confidence: 99%
“…Consent was provided by all guardians in line with the guidelines received from the Research Ethics Committee of the Children, Youth and Women's Health Service, Adelaide, South Australia. Patients were previously genotyped for all known mutations in craniosynostosis‐causing genes FGFR1–3 and TWIST1 (Anderson et al, 2007). Suture tissue was taken from prematurely fused coronal and lambdoid sutures from a patient (male, 7 months) diagnosed with Apert syndrome (AP) and carrying an FGFR2 Ser252Trp mutation.…”
Section: Methodsmentioning
confidence: 99%